Fractional order PID sliding mode control for speed regulation of permanent magnet synchronous motor - Fardila Mohd Zaihidee (Tanjong Malim, 2021)
Fractional order PID sliding mode control for speed regulation of permanent magnet synchronous motor by Fardila Mohd Zaihidee